GLOBAL FINANCIAL CRISIS AND THE EFFECTS OF ITS ON TURKISH ECONOMY - TERZİ, NURAY (VILNIUS GEDIMINAS TECHNICAL UNIV PRESS, TECHNIKA, 2010)
The global economy has experienced a major downturn and sharpest drop in world output since the Great Depression. While the severity and duration of the crisis are still unclear, the major industrial countries are already in or close to recession and the global slowdown are expected to be deeper and much more prolonged than previously anticipated. The global financial crisis has also affected economic activity by moving from the financial sector to the real economy in economies. As the deepening financial crisis intensifies its grip on the global economy, Turkish economy has begun to feel its effects. The aim of this paper is to provide a short insight into the global financial crisis and focus on the effects its on Turkish Economy.
Keywords: global financial crisis; financial crisis; sectoral analysis; economic analysis; Turkey economy